Pengaruh Self Efficacy, Motivasi Kerja, Soft Skill, dan Hard Skill terhadap Kinerja Karyawan PT. Gemilang Adi Perkasa - Obi Nur Romandhon; Agus Budi Santosa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to determine how the performance of PT. Gemilang Adi Perkasa employees is influenced by self-efficacy, work motivation, soft skills, and hard skills. Sample. The population studied in this study was 105 employees of PT Gemilang Adi Perkasa. Sampling was conducted using a saturated sampling technique. This study used primary data with a data hypothesis testing tool using Statistical Product and Service Solutions (SPSS) software version 26, and the data analysis method used was multiple linear regression. The results of partial hypothesis testing indicate that self-efficacy has a positive effect on employee performance. Motivation has a positive and significant effect on employee performance. Soft skills have a positive and significant effect on employee performance. Hard skills have a positive and significant effect on employee performance.